A közös értékteremtés fogalma a szolgáltatástudományban - Garai, Zsolt (Kultúratudományi Szemle, 2022)
Concept of value co-creation in service science Zsolt Garai In this paper I examine the conceptual innovation in service science, related to co-creation of value. To understand better the service logic behind the concept, I first reconstruct the need for such a reform, and I argue that under some interpretations the concept cannot play the role we expect from it. I illustrate the application of these interpretations in a specific domain of its best practices, namely in ITILv3 and ITILv4. Then, to frame and clarify some philosophical underpinnings behind the concept, I relocate the idea into an ancient concept of joint action and friendship. I identify some presuppositions of the idea of collectively shared and created values in virtue of this philosophical analogy, namely concerning its instrumentalism on practical reasoning about ends and values.